Does differential predation of Littorina saxatilis colour morphs contribute to the maintenance of a colour cline? Insights from a field tethering experiment - Gefaell, Juan; Vigo, Ramón; Rolán-Alvarez, Emilio (Journal of Molluscan Studies, 2025)
Colour clines constitute an interesting topic of study for evolutionary ecologists as they allow for the testing of different hypotheses on the adaptive value of colour variation. One possible explanation for the selective advantage of colouration is crypsis. In Littorina saxatilis from the Rías Baixas (northwest Iberian Peninsula), a temporally stable and spatially recurrent colour cline has been described. This cline extends from wave-sheltered localities to the most wave-exposed areas, the latter bearing monomorphic populations of a lineated morph. As the ecological communities, and therefore the background colours, change gradually along the wave-exposure continuum, a plausible explanation for this cline is selection for crypsis, by which less cryptic morphs are weeded out from the populations, presumably by crabs. This would be especially intense at the monomorphic localities along the cline. In the present study, we describe a tethering experiment at a representative wave-exposed site from the Rías Baixas (Cabo Silleiro) aimed at testing this hypothesis, in addition to a series of complementary analyses on Cabo Silleiro and a nearby polymorphic site (Aguncheiro), from which most of the snails used in the experiment were collected. The analysis of Aguncheiro revealed slight differences in the distribution of shell scars (reflecting past crab attacks) across colour morphs, without clear support for the selection for crypsis hypothesis. In the tethering experiment, predation rates by crabs were recorded for three different transplanted colour morphs from Aguncheiro, along with the resident morph from Cabo Silleiro. The results were suggestive, but not conclusive. The presumably more conspicuous morph was more likely to be predated in only one of two sessions and only when classifying both shell chips and more substantive breaks as predation attempts. While limited in power, the results do provide valuable data for designing future experiments and motivation for continued investigation of shell colour morph variation in this organism.
Publisher Copyright: © The Author(s) 2025. Published by Oxford University Press on behalf of The Malacological Society of London.